A trigonometric identity for 2 × 2 block matrices - Withers, Christopher S.; Nadarajah, Saralees (International journal of mathematical education in science and technology, 2015)
This note extends some formulas relating exponential, trigonometric and hyperbolic trigonometric functions to a subset of 2 × 2 block matrices.